Signifikansi Diplomasi Islam Moderat Era Susilo Bambang Yudhoyono Dalam Merespon Problem Keamanan Timur Tengah - Ziyad Falahi (Andalas Journal of International Studies (AJIS))
This article tries to describe the significance of moderate Islam which is becoming a symbol of Indonesian diplomacy during the period of Susilo Bambang Yudhoyono’s administration. Susilo Bambang Yudhoyono’s administration showed optimistic attitude that moderate Islam is the Indonesian strategy to position itself amid the opposition discourse between the West and Islam. But it is interesting to see that the implementation of moderate Islam is actually not on its substance. This can be seen in the case of Israeli-Palestinian conflicts which show the ambivalence of Indonesian position. The inconsistent implementation of moderate Islam can also be seen in the Indonesian position towards Iran's nuclear case. SBY’s administration finally had to change its policies from supporting the UN resolution against Iran then abstained in the next resolution. Thus, the moderate Islam that is only applied in the context of imaging instead became a burden for Indonesia's diplomacy.